Characterization of Staphylococcus aureus isolates from mastitic milk, udder surfaces and milkers’ hands from arid and semi arid regions of India for capsular (cap5K and cap8K) and collagen adhesin (cna) genes - BHATI, TARUNA; KATARIA, A K (The Indian Journal of Animal Sciences, 2019)
Staphylococcus aureus (S. aureus) is an important cause of bovine mastitis. The antiphagocytic capsule of bacteria promotes colonization and persistence on mucosal surfaces while the presence of collagen adhesin (cna gene) is associated with bacterial adhesion in mammary tissues; hence both are regarded as important determinants of virulence. In the present study, 197 samples consisting of mastitic milk, milkers’ hand swabs and udder surface swabs were collected which yielded 107 S. aureus isolates. These S. aureus isolates (107) from different sources of sampling were characterized for their capsular types targeting cap5K and cap8K genes in a duplex PCR along with amplification of cna gene. Majority of the isolates (67.6%) possessed cap5K gene with a lower percentage (22.9%) of isolates carrying cap8K gene and 9.5% carrying both the genes. Moreover, cap5K gene was predominant in isolates from milkersâ€™ hands (85.7%) while cap8K gene was more common in bovine udder isolates (41.2%). cna gene was observed in 27.6% isolates with highest occurrence in milk isolates (44.8%) compared to udder (37.9%) and milkers’ hand (17.2%). cna positive isolates carried cap8K gene (66.7%) and were significantly associated with both cap5k and cap8k genes. In conclusion, the majority of the S. aureus isolates of mastitis obtained from arid and semi arid zones of India possessed the genes for capsule production, and cap5K was the predominant gene. The cna gene for collagen adhesion was observed in fewer isolates with significant association with cap8K gene.